The effect of cCMP and cUMP on growth of Pseudomonas aeruginosa - Risser, Christoph; Rothschuh, Justin; Bähre, Heike; Neumann, Detlef; Seifert, Roland; Schirmer, Bastian (Frontiers in Microbiology, 2025)
The aim of this study was to screen for possible biological effects of the non-canonical nucleotides 3’,5’-cyclic uridine monophosphate (cUMP) and 3’,5’-cyclic cytidine monophosphate (cCMP) on Pseudomonas aeruginosa beyond the already reported function in the bacterial pyrimidine cyclase system for antiphage resistance (Pycsar). Since endogenously synthesized cCMP was detected in growing bacterial cultures and the cCMP concentration was higher when nutrients became more restricted, we hypothesized that a membrane-permeable analog of cCMP added to growing cultures alters growth kinetics. Indeed, when growing in a nutrient-scarce minimum salt medium, the cCMP analog acetoxymethyl-cCMP led to a dose-dependent growth lag, whereas neither its native counterpart nor cAMP, cGMP, or cUMP induced such a lag. This inhibitory effect on growth translated into a sensitizing effect against the antibacterial drugs azithromycin and, very pronounced, against gentamicin. Since P. aeruginosa is one of the most common opportunistic pathogens, improving antibacterial drug therapies is of high interest and may be a promising future research area. Exposure of bacterial cultures to native cUMP led to induction of biofilm formation, which was paralleled by an increase in c-di-GMP synthesis and generation of the Quorum sensing metabolites pqs and hhq. Since biofilm formation is another key feature of Pseudomonas aeruginosa to evade the host’s immune system, targeting cyclic UMP concentrations during infections may also be of therapeutic relevance. In summary, our findings corroborate the need for further research on the 3’,5’-cyclic pyrimidine nucleotides in bacteria beyond their established function in the Pycsar anti-phage defense system.